(untitled) - Shipton, Paul (London, 2001)
On the night of 14 April, 1912, the ship Titanic hit an iceberg and sank. It was on its first voyage across the Atlantic and many people died. But what really happened? Why did the ship hit an iceberg? Why didn't another ship save the passengers? Although the disaster happened over 80 years ago, there are still people who can remember it and it still has the power to capture the imagination.
Keywords: Titanic (steamship); Juvenile literature; North atlantic ocean